2012
DOI: 10.2214/ajr.11.8347
|View full text |Cite
|
Sign up to set email alerts
|

An Intravoxel Incoherent Motion Diffusion-Weighted Imaging Study of Prostate Cancer

Abstract: IVIM DWI parameters are significantly different between prostate cancer and PZ. IVIM DWI may offer additional information for tissue characterization in the prostate gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 25 publications
6
81
0
2
Order By: Relevance
“…During our scanning, the TE was not constant for each patient because of irregular respiration or variations in liver sizes. Another interpretation is that f is potentially sensitive to other bulky flow information, such as excretion of granules or glands, diffusion direction or diffusion pattern, and is not specific to perfusion uniquely (35)(36)(37). FNH contains bile ducts; therefore, after taking up a hepatocyte-specific contrast agent, delayed biliary excretion is possible.…”
Section: Discussionmentioning
confidence: 99%
“…During our scanning, the TE was not constant for each patient because of irregular respiration or variations in liver sizes. Another interpretation is that f is potentially sensitive to other bulky flow information, such as excretion of granules or glands, diffusion direction or diffusion pattern, and is not specific to perfusion uniquely (35)(36)(37). FNH contains bile ducts; therefore, after taking up a hepatocyte-specific contrast agent, delayed biliary excretion is possible.…”
Section: Discussionmentioning
confidence: 99%
“…9 MRI data for 26 cases of histologically proven prostate cancer was used. MR images were acquired with a 3T scanner (Achieva, Philips Healthcare) using a six-channel phased array coil.…”
Section: Mri Examinationmentioning
confidence: 99%
“…In prostate cancer, IVIM-derived variables (i.e. molecular diffusion coefficient D, and perfusion fraction f) were shown to be significantly lower than in benign prostate tissue [3536]. Others found that high-grade prostate cancers had significantly lower D-values than low-grade lesion, allowing for a more accurate estimation of tumor grade than ADC [37].…”
Section: Dw-mri As a Tool For Risk-assessmentmentioning
confidence: 99%
“…Others found that high-grade prostate cancers had significantly lower D-values than low-grade lesion, allowing for a more accurate estimation of tumor grade than ADC [37]. In another analysis, however, f and the perfusion-related diffusion coefficient (D*) were not significantly different in prostate cancer and benign prostatic hyperplasia [36] and further research will have to identify the true clinical value of this novel technique. Diffusion kurtosis imaging (DKI) is a DWI-technique that takes into account that water molecules in biological tissues do not follow a Gaussian pattern of distribution.…”
Section: Dw-mri As a Tool For Risk-assessmentmentioning
confidence: 99%